The sigma factor sigma s affects antibiotic production and biological control activity of Pseudomonas fluorescens Pf-5. - Sarniguet, A (1995)
Pseudomonas fluorescens Pf-5, a rhizosphere-inhabiting bacterium that suppresses several soilborne pathogens of plants, produces the antibiotics pyrrolnitrin, pyoluteorin, and 2,4-diacetylphloroglucinol. A gene necessary for pyrrolnitrin production by Pf-5 was identified as rpoS, which encodes the stationary-phase sigma factor sigma s. Several pleiotropic effects of an rpoS mutation in Escherichia coli also were observed in an RpoS- mutant of Pf-5. These included sensitivities of stationary-phase cells to stresses imposed by hydrogen peroxide or high salt concentration. A plasmid containing the cloned wild-type rpoS gene restored pyrrolnitrin production and stress tolerance to the RpoS- mutant of Pf-5. The RpoS- mutant overproduced pyoluteorin and 2,4-diacetyl-phloroglucinol, two antibiotics that inhibit growth of the phytopathogenic fungus Pythium ultimum, and was superior to the wild type in suppression of seedling damping-off of cucumber caused by Pythium ultimum. When inoculated onto cucumber seed at high cell densities, the RpoS- mutant did not survive as well as the wild-type strain on surfaces of developing seedlings. Other stationary-phase-specific phenotypes of Pf-5, such as the production of cyanide and extracellular protease(s) were expressed by the RpoS- mutant, suggesting that sigma s is only one of the sigma factors required for the transcription of genes in stationary-phase cells of P. fluorescens. These results indicate that a sigma factor encoded by rpoS influences antibiotic production, biological control activity, and survival of P. fluorescens on plant surfaces.